2010
DOI: 10.3109/00016480903124655
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of hearing loss from trauma and inflammation: otoprotective therapies from the laboratory to the clinic

Abstract: This article reviews a series of in vitro and in vivo studies that examined the otoprotective efficacy of locally delivered dexamethasone and explored the mechanisms by which dexamethasone protects auditory hair cells. These studies used auditory threshold testing in response to pure tone stimuli, organ of Corti explant cultures, FITC-phalloidin-stained explants, and surface preparations to determine hair cell density, osmotic pump delivery of dexamethasone into the scala tympani, an animal model of electrode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Cytokine-exposed explants treated with DXM prevented TNFa-induced loss of auditory hair cells and resulted in the downregulation of Bax gene expression with upregulation of both Bcl-2 and Bcl-xl gene expression compared with baseline levels of gene expression in control explants and with the expression levels of the housekeeping gene, β -actin. Biopolymer- (i.e., poly(styrene-b-isobutylene-b-styrene); SIBS) eluted DXMb retains its ability to prevent the death of explant auditory hair cells that were exposed to TNFa and to initiate the same patterns of upregulation and downregulation of antiapoptosis- and proapoptosis-related genes (i.e., Bcl-2, Bcl-xl, and Bax) that were observed in TNFa-challenged and TNFa-challenged, DXM-treated organ of Corti explants [54].…”
Section: Resultsmentioning
confidence: 99%
“…Cytokine-exposed explants treated with DXM prevented TNFa-induced loss of auditory hair cells and resulted in the downregulation of Bax gene expression with upregulation of both Bcl-2 and Bcl-xl gene expression compared with baseline levels of gene expression in control explants and with the expression levels of the housekeeping gene, β -actin. Biopolymer- (i.e., poly(styrene-b-isobutylene-b-styrene); SIBS) eluted DXMb retains its ability to prevent the death of explant auditory hair cells that were exposed to TNFa and to initiate the same patterns of upregulation and downregulation of antiapoptosis- and proapoptosis-related genes (i.e., Bcl-2, Bcl-xl, and Bax) that were observed in TNFa-challenged and TNFa-challenged, DXM-treated organ of Corti explants [54].…”
Section: Resultsmentioning
confidence: 99%
“…Studies reported that in situations with acoustic overstimulation, not only inflammatory responses but also oxidative stress can be involved in the induction of auditory hair cell apoptosis [15,17]. In this sense, it is widely accepted that TNFα is a pro-inflammatory cytokine that, among other properties, can induce auditory hair cell apoptosis through the extrinsic cell death pathway [14].…”
Section: Discussionmentioning
confidence: 99%
“…One factor that reduces the durability of the implant is again fibrosis, i.e., the growth of connective tissue around the electrodes after insertion of the CI into the inner ear. Because of their hair cell-protecting properties in combination with an antiproliferative effect on fibroblasts, glucocorticoids such as dexamethasone (DMS) are often administered via injection in conjunction with the implantation procedure [20,55]. To better control the drug concentration in the therapeutic window, we developed a CI-associated LDD system based on DMS.…”
Section: Cochlear Implantsmentioning
confidence: 99%